1997
DOI: 10.1093/njaf/14.4.165
|View full text |Cite
|
Sign up to set email alerts
|

Snags and Down Wood in Missouri Old-Growth and Mature Second-Growth Forests

Abstract: As forest managers in the Midwest focus more attention toward understanding and maintaining ecosystem processes, greater emphasis is being placed on the role of snags and down wood in providing wildlife habitat, cycling nutrients, and maintaining continuity in forest structure following harvest. We measured five remnant old-growth hardwood tracts and six mature, second-growth, hardwood tracts in Missouri and compared findings concerning (1) the volume of down wood and (2) the number and size distribution of sn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 0 publications
2
5
0
1
Order By: Relevance
“…The projected area of CWD (an estimate of log surface area potentially available for seedling establishment) of 252.2 m 2 /ha (2.52% of ground surface) found in this study is similar to that reported from forests of the central or eastern North America (MacMillan 1981;Shifley et al 1997), yet is substantially lower than that reported from northwestern North America, where CWD can cover from 10 to 25% of the forest floor (see Harmon and Sexton 1995;Clark et al 1998).…”
Section: Pre-harvest Cwd Measuressupporting
confidence: 83%
“…The projected area of CWD (an estimate of log surface area potentially available for seedling establishment) of 252.2 m 2 /ha (2.52% of ground surface) found in this study is similar to that reported from forests of the central or eastern North America (MacMillan 1981;Shifley et al 1997), yet is substantially lower than that reported from northwestern North America, where CWD can cover from 10 to 25% of the forest floor (see Harmon and Sexton 1995;Clark et al 1998).…”
Section: Pre-harvest Cwd Measuressupporting
confidence: 83%
“…The primary goal of our study was to evaluate the impacts of harvest on sizes and allocation of C pools within forests of the Missouri Ozarks. Indeed, the stem density (401-1761 individualsÁha -1 ) and basal area (8.9-27.0 m 2 Áha -1 ) fell within the ranges of values reported by other studies of similar forests in this region (Weaver and Ashby 1971;Muller 1982;Shifley et al 1997). Unfortunately, comparisons of our C pool components to other studies were hampered because C pool estimates are differently influenced by sitespecific disturbance regimes and the definitions of some major C pools vary, especially for dead organic matter (Grier and Logan 1977;Matthews 1997;Schlesinger 1977).…”
Section: Discussionsupporting
confidence: 63%
“…Various natural processes and forest-management activities can affect snag abundance and size distribution. In the absence of large-scale mortality events such as ice storms, disease outbreaks, or wildfire, the diameter distribution of snags in the southeastern US may resemble that of live trees in mature forests, with most snags being in the smaller size classes in unthinned stands (McComb and Muller 1983;Shifley et al 1997;Moorman et al 1999). However, snags may represent only 5%-14% of the total number of stems (McComb and Muller 1983;Shifley et al 1997).…”
Section: Introductionmentioning
confidence: 99%